Pengaruh Motivasi Karir, Motivasi Pemahaman dan Faktor Lingkungan Keluarga Terhadap Minat Menjadi Profesi Akuntan (Chartered Accountant) - Novia Putri Pitaloka; Bambang Widarno (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This study aims to examine the influence of Career Motivation, Understanding of Motivation, and Family Environmental Factors on Interest in Becoming a Public Accountant. This study was conducted at Slamet Riyadi University and Sebelas Maret State University. The data used are quantitative. The data source is primary data. The entire population in this study was 1,330 accounting students at Slamet Riyadi University and Sebelas Maret State University. The sample used was 93 respondents. The sampling technique used was the Solvin equation and was tested using SPSS version 25. Data analysis techniques were descriptive tests, independent sample t-tests, validity tests, reliability tests, classical hypothesis tests, multiple linear regression tests, hypothesis tests, and model tests. The results of this study indicate that: (1) Career Motivation has a positive and significant influence on Interest in Becoming a Public Accountant, (2) Understanding of Motivation has a positive and significant influence on Interest in Becoming a Public Accountant, (3) Family Environmental Factors have a positive and significant influence on Interest in Becoming a Public Accountant